No easy harvest the dilemma of agriculture in underdeveloped countries - Millikan, Max F.; Massachusetts Institute of Technology. Center for International Studies; Conference on Productivity and Innovation in Agriculture in the Underdeveloped Countries, Dedham, Mass., 1964. (Boston Little, Brown, 1967)
A revision and extension of the report of the Conference on Productivity and Innovation in Agriculture in the Underdeveloped Countries, held at Dedham, Massachusetts, from June 29 through August 7, 1964.
Keywords: Agriculture -- Economic aspects -- Developing countries; Agriculture -- Developing countries